Extrapyramidal effects and nutritional state associated with the use of antipsychotics in patients hospitalized in a psychiatric reference hospital, Belém-Pará (Research, Society and Development, 2022)
The schizophrenia is a serious/chronic mental disorder, characterized by disorders of thought, emotions and feelings, in which it compromises social interaction in various spheres. With the advent of psychopharmacotherapy in the 50 years of the last century, it represented a real revolution in the care of those who suffer from mental disorders. This study aimed to: evaluate the interference of the extrapyramidal effects caused by antipsychotics on the motor alteration and on the nutritional status of schizophrenic patients admitted to a psychiatric reference hospital. The research field was the Psychiatric Clinic of the State Public Foundation Hospital de Clínicas Gaspar Vianna, being performed with patients with schizophrenia, admitted to the Short Hospitalization Service, from August 2018 to February 2019. To assess the extrapyramidal effects, a pre-adapted form was used, based on the Simpson-Angus scale (Extrapyramidal effects scale) and the Barnes scale (Barnes akathisia scale). The anthropometric evaluation consisted of the body mass index, tricipital skinfold and waist circumference. For static analysis of data was performed the anova test and Pearson correlation test considering a p